Compared to what?: An introduction to the analysis of algorithms - Gregory J. E Rawlins (Computer Science Press, 1991)
The book covers a segment of the classical material on data structures and algorithms. It covers all the essentials of algorithms analyisis in an innovative problem-oriented style; focuses on the basic programming problem and works through a variety of options for its solution rather than simply stating a correct answer